A literature study of ICT usage in construction project / Mohd Farhan Mohd Mukelas and Emma Marinie Ahmad Zawawi - Mohd Mukelas, Mohd Farhan; Ahmad Zawawi, Emma Marinie (2012)
This paper presents literature of ICT usage in construction project. The objective of this study are to identify the type of ICT can be used in construction industry, to identify the ICT implementation constrains and benefits against construction, and to analyze the training of ICT program. The study revealed that there were 17 types of ICT application identified which could be used during construction process, for example e-tendering system used for contractor to find open tender electronically. In addition, 3 ICT training characteristic were found:There are Training company support, ICT training mode preferences, and ICT competences expectation. Eventually 15 benefits were found by adopting ICT in construction projects. One example is ICT application lead to time saving. Meanwhile only 7 weaknesses were identified: one of them is ICT software is costly. This research also aims to produce framework of ICT development plan by conducting a survey among Malaysian construction organization in order to seek for actual ICT status and their plan for improvement.